LITERATURE REVIEW RISK FACTOR OF LOWER BACK PAIN IN OFFICE WORKERS WITH VIDEO DISPLAY TERMINAL (VDT) - Yosephin Sri Sutanti; Ruth Mary Kasan; Johannes Hudyono; Yusuf Handoko (Dinasti Publisher, 2022)
Lower back pain (LBP) has become the most common musculoskeletal condition in developing countries. In Indonesia, it ranges from 3-17% affected by LBP. This is also related to the use of Visual Display Terminal (VDT), because the use of VDT is also related to one's sitting position. It is also known that, LBP is the third leading cause of occupational diseases caused by using VDT. Literature reviews that are based on articles and journals customized to PICO (population, intervention, control, output). Journals were searched in medical databases through Google Scholar, JOEM, and the Cochrane Library, using the keywords